2019
DOI: 10.3389/fgene.2019.00875
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Pale-Yellow Coat Color of Rabbits Generated viaMC1R Mutation With CRISPR/Cas9 System

Abstract: Coat color is of great importance in animal breed characteristics; it is not only a significant productive trait but also an indispensable economic trait, especially in the rabbit industry. In the present study, the relationship between melanocortin 1 receptor (MC1R) genotypes and coat color phenotypes was observed in five rabbit breeds with popular coat colors that are present in China. These breeds comprised the Lianshan black rabbit (BR), Fujian yellow rabbit (YR), New Zealand white rabbit (WR), Gray Giant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Spontaneous mutations in rabbits can be found accidentally and they can be used in controlling the coat color for commercial purposes such as tyrosinase and the melanocortin 1 receptor (Aigner et al, 2000 ; Xiao et al, 2019 ). However, some spontaneous mutations in rabbits can cause a pronounced phenotype that can mimic human diseases, such as Watanabe heritable hyperlipidemic (WHHL) rabbits (Watanabe, 1980 ), St. Thomas hyperlipidemic rabbits (Laville et al, 1987 ; Seddon et al, 1987 ) and complement 6 deficient rabbits (Rother, 1986 ; Liu et al, 2007a ).…”
Section: “Naturally” Genetically Modified Rabbitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous mutations in rabbits can be found accidentally and they can be used in controlling the coat color for commercial purposes such as tyrosinase and the melanocortin 1 receptor (Aigner et al, 2000 ; Xiao et al, 2019 ). However, some spontaneous mutations in rabbits can cause a pronounced phenotype that can mimic human diseases, such as Watanabe heritable hyperlipidemic (WHHL) rabbits (Watanabe, 1980 ), St. Thomas hyperlipidemic rabbits (Laville et al, 1987 ; Seddon et al, 1987 ) and complement 6 deficient rabbits (Rother, 1986 ; Liu et al, 2007a ).…”
Section: “Naturally” Genetically Modified Rabbitsmentioning
confidence: 99%
“…The transgenic constructs are typically composed of the transgene (either cDNA or genomic DNA) under the control of a tissue-specific promoter such as liver-and macrophage-specific promoter. In addition to the pronuclear microinjection method, other methods such as sperm vector (Wang et al, 2003;Li et al, 2006Li et al, , 2010Shen et al, 2006), ICSI-mediated transgenesis (Li et al, 2010;Zhang et al, 2016), somatic cell nuclear transfer (SCNT) (Li et al, 2009) or chimeric SCNT (Matsuda et al, 2002;Skrzyszowska et al, 2006), lentiviral vectors (Hiripi et al, 2010), transposonmediated transgenesis (Katter et al, 2013;Ivics et al, 2014), and novel genome editing technology (Song J. et al, 2016;Yang et al, 2016;Li et al, 2019) have been reported to produce Tg rabbits. In spite of this, the pronuclear microinjection is still the most common method even though transgene integration rate is low.…”
Section: Transgenic Rabbitsmentioning
confidence: 99%
“…In this study, two indels (c.284-285del and c.292-295del) were found in the TB and SW breeds, and polymorphism distribution of the c.292-295del sites were significantly different between TBs and SWs ( p < 0.05). Previous investigations found that MC1R c.280_285del6 was more frequently presented in black rabbits, c.304_333del30 was recessive red/yellow, and c.[124A;125_130del6] was connected with Japanese brindling coat color [ 6 , 7 , 30 ]. The MITF gene polymorphism is known to be associated with the black and white colors in mice [ 31 ], pigs [ 32 ], cattle [ 33 ], horses [ 34 ], chickens [ 35 ], ducks [ 36 ], llamas [ 37 ], and so on.…”
Section: Discussionmentioning
confidence: 99%
“…They have shown that the Gray Giant rabbit has an E allele, whereas the New Zealand White rabbit, the Checkered Giant rabbit and the Lianshan Black rabbit have a 6 bp in‐frame deletion (Xiao et al . 2019). The experimental MC1R ko causes the blockage of the synthesis of eumelanin and has created a novel pale‐yellow coat color.…”
Section: Properties Of the Rabbit Hair Coatmentioning
confidence: 99%